Maia - Diaz, Gloria Cecilia; Rosero, Jose (Mexico, D. F. : Ediciones Castillo, Grupo Macmillan, 2013)
La gata Ioda, mascota de Maia, sufre un accidente en la calle y despues de ser examinada por el veterinario, decide amputarle una pata. Maia piensa que la papa de Ioda volvera a crecer y se niega a aceptar su cojera. En la escuela, Maia conoce a Matias, un nuevo companero con una discapacidad fisica. El es alegre y desenvuelto, a pesar de su condicion. Sera posible que pase algo similar con Ioda?"--Pagina 4 de la portada.
Maia's pet cat, Ioda, suffers from an accident on the street. After being examined by the vet, it is decided that the cat's leg needs to be amputated. Maia thinks that Ioda's leg will start growing again and she will not accept her lameness. At school Maia meets Matias, a new classmate with a physical disability. He is happy and jaunty, in spite of his condition. Would it be possible that something similar could happen to Ioda?
Edad lectora 8+.
In Spanish.
Keywords: Cats -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Animals with disabilities -- Juvenile fiction; Children with disabilities -- Juvenile fiction; Gatos -- Novela juvenil; Relaciones de amistad entre animales y seres humanos -- Novela juvenil; Ninos discapacitados -- Novela juvenil; Spanish language materials; Libros de lectura elementales